2017
DOI: 10.21037/jtd.2017.01.17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between radiologic patterns, pulmonary function values and bronchoalveolar lavage fluid cells in newly diagnosed sarcoidosis

Abstract: Background: The aim of the present study was to identify specious radiologic and/or physiologic prognostic marker(s), which lead to optimize of the patient follow-up frequency. Methods: Eighty consecutive patients with newly diagnosed pulmonary sarcoidosis. Patients underwent chest radiography, high-resolution computed tomography (HRCT) examination, pulmonary function tests (PFT), bronchoscopy with bronchoalveolar lavage (BAL) and lung biopsy, and bronchoalveolar lavage fluid (BALF) cell examination. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
(49 reference statements)
0
22
0
1
Order By: Relevance
“…28 Approximately 200 cells were counted in each sample and classified as neutrophils, lymphocytes, and macrophages according to morphological characteristics. 29…”
Section: Methodsmentioning
confidence: 99%
“…28 Approximately 200 cells were counted in each sample and classified as neutrophils, lymphocytes, and macrophages according to morphological characteristics. 29…”
Section: Methodsmentioning
confidence: 99%
“…We had performed literature search looking for a cellular markers that could help to predict the course of sarcoidosis and selected four molecules, e.g., CD31, CD38, CD44, and CD103. Many inflammatory cells and tissue cells with various, sometimes even opposite effects may be positive for CD31, CD38, CD44, and CD103 (23)(24)(25)(26)(27)(28)(29), but while sarcoidosis is driven by T-cell mechanisms, particularly the accumulation of activated CD4 T-cells in the lungs, allowing for T-cell attachment and transmigration through the endothelium (30)(31), research was performed on T cell subpopulations CD4 + and CD8 + . CD31, also known as platelet endothelial cellular adhesion molecule-1 (PECAM-1), is an integral membrane protein expressed by endothelial cells, platelets, dendritic cells, and blood cells, including T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Levy et al recommend repeated HRCT scans if the clinical image changes or complications are suspected [36 37]. Unlike X-ray scans, some lesions visible in HRCT demonstrate a relationship with pulmonary function disorders [38][39][40]. Drent et al demonstrated correlations between features visible in HRCT such as thickening of the bronchovascular bundle, intraparenchymal nodules, septal and non-septal lines, or focal pleural thickening on one hand, and results of respiratory functional tests on the other [38].…”
Section: High Resolution Computed Tomographymentioning
confidence: 99%